Guidelines for Teachers’ Competency Management of Learning Experience at Ban Paen Subdistrict Municipality Kindergarten School - Yaidee , Panyaphol; Pakdee, Chalee (MCU Haripunchai Review, 2026)
This research aimed to: 1) examine the current state of competency management for learning experience provision among teachers at Ban Paen Municipal Kindergarten, Mueang District, Lamphun Province, and 2) identify guidelines for managing teacher competency in learning experience provision at Ban Paen Municipal Kindergarten, Mueang District, Lamphun Province. This qualitative study included 19 key informants: administrators, teachers, parents, and educational personnel. Research instruments consisted of interview guides and focus group discussion guides. Data were analyzed using content analysis. The findings revealed: 1)Regarding the current state of competency management for learning experience provision among teachers at Ban Paen Municipal Kindergarten: All five dimensions of early childhood teacher competency contributed to “excellent” levels of learning management quality and child development. Strengths included the use of Active Learning, technology integration, and a PLC organizational culture. However, some limitations remained in terms of teaching materials, workload, and record-keeping. The school should utilize in-depth student data, conduct classroom research, and assess individual teacher competencies. 2)Guidelines for managing teacher competency in learning experience provision at Ban Paen Municipal Kindergarten, Mueang District, Lamphun Province: Planning phase (P) – the school establishes shared goals and vision between administrators and teachers. Implementation phase (D) – focuses on teacher development according to plan using a systems management approach, applies the Deming cycle in positive classroom environments, and arranges atmosphere and technology conducive to learning based on Constructionism principles. Monitoring and evaluation phase (C) – continuous assessment of teacher competency through record-keeping systems such as portfolios and reflective practices. Improvement and development phase (A) – evaluation results inform individual teacher development plans (ID Plans) linked to internal supervision and knowledge exchange through PLCs to enhance teaching quality and achieve sustainable student development.